Forms and Mechanisms of Commercialization of Intellectual Capital of Universities and Research Institutes - Oganov, Sergo (YSU Journal of International Affairs, 2023)
The new economic reality, which dictates new development imperatives, highlights the role of intellectual property. Intellectual property, becoming a new driver of development, highlights the role of universities and research institutes, which are considered capitals of knowledge creation. The need for intellectual property management is driven by globalization and the growth of the knowledge economy, which aims to transform products and services into commercially viable value. The new created economic reality makes it imperative to increase the role of knowledge creation capitals, such as universities. Universities are gradually replacing the traditional function of research, teaching and knowledge dissemination with a new, more advanced role that contributes to the creation of a business-academic model. In the 21st century, research universities are the main capital of knowledge creation, promoting economic development based on scientific and technological progress, in which the role of knowledge-based factors is important to promote the forefront of the economy, they are the creation of highly trained human capital and the commercialization of research. For the effective operation of university intellectual capital, it is necessary to interpret the concept of "intellectual capital", to present the forms and mechanisms of commercialization, which we will study in this article.